MicroRNA‐375‐3p enhances chemosensitivity to 5‐fluorouracil by targeting thymidylate synthase in colorectal cancer - Xu, Fei; Ye, Ming‐Liang; Zhang, Yu‐Peng; Li, Wen‐Jie; Li, Meng‐Ting; Wang, Hai‐Zhou; Qiu, Xiao; Xu, Yan; Yin, Jin‐Wen; Hu, Qian; Wei, Wan‐Hui; Chang, Ying; et al. (Cancer science, 2020)
Resistance to chemotherapy is a major challenge for the treatment of patients with colorectal cancer (CRC). Previous studies have found that microRNAs (miRNAs) play key roles in drug resistance; however, the role of miRNA‐373‐3p (miR‐375‐3p) in CRC remains unclear. The current study aimed to explore the potential function of miR‐375‐3p in 5‐fluorouracil (5‐FU) resistance. MicroRNA‐375‐3p was found to be widely downregulated in human CRC cell lines and tissues and to promote the sensitivity of CRC cells to 5‐FU by inducing colon cancer cell apoptosis and cycle arrest and by inhibiting cell growth, migration, and invasion in vitro. Thymidylate synthase (TYMS) was found to be a direct target of miR‐375‐3p, and TYMS knockdown exerted similar effects as miR‐375‐3p overexpression on the CRC cellular response to 5‐FU. Lipid‐coated calcium carbonate nanoparticles (NPs) were designed to cotransport 5‐FU and miR‐375‐3p into cells efficiently and rapidly and to release the drugs in a weakly acidic tumor microenvironment. The therapeutic effect of combined miR‐375 + 5‐FU/NPs was significantly higher than that of the individual treatments in mouse s.c. xenografts derived from HCT116 cells. Our results suggest that restoring miR‐375‐3p levels could be a future novel therapeutic strategy to enhance chemosensitivity to 5‐FU. Resistance to chemotherapy is a major challenge for the treatment of patients with colorectal cancer (CRC). Our results suggest that the restoration of microRNA‐375‐3p levels could be a future novel therapeutic strategy to modulate and enhance chemosensitivity to 5‐fluorouracil treatment in CRC.